Graphene quantum dots coated VO2 arrays for highly durable electrodes for Li and Na Ion batteries - Xia, Xinhui (2015)
Nanoscale surface engineering is playing important role in enhancing the performance of battery electrode. VO2 is one of high-capacity but less-stable materials and has been used mostly in the form of powders for Li-ion battery cathode with mediocre performance. In this work, we design a new type of binder-free cathode by bottom-up growth of biface VO2 arrays directly on a graphene network for both high-performance Li-ion and Na-ion battery cathodes. More importantly, graphene quantum dots (GQDs) are coated onto the VO2 surfaces as a highly efficient surface “sensitizer” and protection to further boost the electrochemical properties. The integrated electrodes deliver a Na storage capacity of 306 mAh/g at 100 mA/g, and a capacity of more than 110 mAh/g after 1500 cycles at 18 A/g. Our result on Na-ion battery may pave the way to next generation postlithium batteries.